Influence of dried distiller grains with solubles in replacement of soybean meal in Boer goat diets - Sardella, Clayton A.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
The purpose of this study was to determine the levels of dried distillers grain with solubles (DDGS) as replacement for soybean meal (SBM) in a Boer goat diet. Our hypothesis was that with the replacement of SBM with DDGS would not influence the goat performance but would reduce cost. Forty-eight meat goat kids (approximately 70 d of age) were used in a completely randomized design. The beginning body weight (BW) was similar across all the treatments (P=0.99). Animals were housed at the KSU Sheep and Meat Goat Center with 3 kids per pen (4 pens per treatment). Kids were housed allotted into one of four experimental diets: 1) 0% SBM replaced by DDGS; 2) 33% SBM replaced by DDGS; 3) 66% SBM replaced by DDGS; and 4) 100% SBM replaced by DDGS. For producers if you feed the control group it will cost you $162 compared to our 100% SBM replaced by DDGS that will cost you $135. These diets were fed in a self-feeder that gave access of pelleted diet and there was continued clean fresh water through the treatment. All diets were pelleted at the Kansas State University feed mill, with pellets containing roughage, so no supplemental forage was needed. We calculated the average daily feed intake (ADFI) and feed efficiency (G:F). Diets were fed for 42 days, with average daily gain (ADG), ADFI, and G:F calculated every week. Upon completion of the experiment, two kids per pen were slaughtered with carcass data collected, including hot carcass weight, yield, loin eye area, loin eye depth, fat depth at the 13th rib, and body wall thickness. Data was analyzed using the GLIMMIX procedure of SAS (SAS Inst., Cary, NC) with pen serving as the experimental unit. The results of this study were that both ADG (P=0.006) and G:F (P=0.005) linearly with increasing DDGS in place of SBM. However, there was no effect from DDGS on BW, ADFI, and any carcass data. The results confirm producers can replace 100% SBM with DDGS without affecting growth performance and can save the producer $27.27 per ton in feed cost.
Keywords: Spring 2018